Treatment of patients with unilateral posterior crossbite in the student clinic in Tromsø : evaluation of treatment outcome and documentation practice in Universitetsklinikken, UTK - Hovden, Elin Marie Bjørnsdatter; Bårdsen, Lisa-Marie (Universitetet i Tromsø, 2012)
The aim of this study was to evaluate the outcome of treatment of unilateral posterior crossbite and factors related to the treatment outcome in patients treated in the University student clinic. Another aim was to evaluate the adequacy and quality of documentation of the posterior crossbite treatments.